Woody climbers show greater population genetic differentiation than trees: Insights into the link between ecological traits and diversification. (18th October 2016) - Gianoli, Ernesto; Torres‐Díaz, Cristian; Ruiz, Eduardo; Salgado‐Luarte, Cristian; Molina‐Montenegro, Marco A.; Saldaña, Alfredo; Ríos, Rodrigo S.
Abstract : The climbing habit is a key innovation in plants: climbing taxa have higher species richness than nonclimbing sister groups. We evaluated the hypothesis that climbing plant species show greater among‐population genetic differentiation than nonclimber species. We compared the among‐population genetic distance in woody climbers (eight species, 30 populations) and trees (seven species, 29 populations) coexisting in nine communities in a temperate rainforest. We also compared within‐population genetic diversity in co‐occurring woody climbers and trees in two communities. Mean genetic distance between populations of climbers was twice that of trees. Isolation by distance (increase in genetic distance with geographic distance) was greater for climbers. Climbers and trees showed similar within‐population genetic diversity. Our longevity estimate suggested that climbers had shorter generation times, while other biological features often associated with diversification (dispersal and pollination syndromes, mating system, size, and metabolic rate) did not show significant differences between groups. We hypothesize that the greater population differentiation in climbers could result from greater evolutionary responses to local selection acting on initially higher within‐population genetic diversity, which could be driven by neutral processes associated with shorter generation times. Increased population genetic differentiation could be incorporated as another line of evidence when testing for key innovations.